Combination therapy with riociquat and inhaled treprostinil in inoperable and progressive chronic thromboembolic pulmonary hypertension - John W. Swisher, PhD, MD; Dillon Elliott, PharmD, BCPS, BCCCP (Respiratory Medicine Case Reports, 2017)
Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by formation of chronic, organized thrombus in pulmonary arteries resulting in development of pulmonary hypertension. We describe the favorable recovery of a patient with inoperable CTEPH treated with combination riociguat and inhaled treprostinil. The patient is a 77 year old female who presented with bilateral pulmonary emboli and was anticoagulated with warfarin for six months. One year later the patient developed recurrent dyspnea and multiple bilateral pulmonary emboli were again noted. Pulmonary arterial pressure (PAP) was estimated at 91 mmHg by echocardiography. The patient was treated with warfarin and sildenafil. Eighteen months later the PAP was estimated at 106 mmHg with significant right ventricular enlargement. The patient was referred to our center for pulmonary hypertension consultation. Right heart catheterization confirmed severe pulmonary hypertension with preserved cardiac output. The patient was not a candidate for thromboendarterectomy due to the peripheral location of chronic obstructing thrombi. Systemic prostacyclin therapy was declined by the patient. Inhaled treprostinil was added to sildenafil and warfarin. The patient maintained good performance status for 2 years, but then developed progressive activity limitation with depressed cardiac output on right heart catheterization. Systemic prostacyclin therapy was declined again. Sildenafil was replaced with riociguat, and 1 year later the patient demonstrated significant recovery of functional capacity and improved hemodynamic profile. We describe significant recovery in a patient with inoperable, progressive CTEPH treated with riociguat and inhaled treprostinil after failing sequential addition of sildenafil and inhaled treprostinil to warfarin. The reported benefits may relate to riociguat's ability to directly stimulate production of cyclic GMP independent of nitric oxide levels in pulmonary artery smooth muscle. There may also be a unique interaction between riocguat and treprostinil that enhanced treatment outcome. Further investigation of this combination of agents may be warranted.